Investigação dos efeitos neurofarmacológicos de Stemodia maritima (linn): alterações comportamentais e avaliação do estresse oxidativo - Sousa, Rayane Siqueira de (2017)
Neurobehavioral disorders are composed of a group of neurological deficiencies, which are associated with both, permanent brain diseases as well as transient brain diseases and/or injury. Among these disorders, depression and anxiety can be highlighted. Studies show that plants of the Stemodia genus are used in the treatment of diseases in traditional medicine. Stemodia maritima Linn. presents an antimicrobial, anti-inflammatory and antioxidant action. Literature reports for this species the presence of a structural variety of constituents, especially steroid class, flavonoids and terpenes, mainly diterpenes. This study investigated the action of ethanolic extract of S. maritima (Sm) in the central nervous system (CNS), with possible neuropsychopharmacological effect and evaluation of oxidative stress in animal models of anxiety and depression. Male swiss mice (25-35 g) were treated acutely with Sm (1, 10 and 100 mg/kg i.p.) or vehicle (5% DMSO) and were subjected to preliminary neuropsychopharmacological analysis. Other groups of animals were treated subchronic with Sm (2.5, 5, 10 and 20 mg / kg - 14 days/ip) or vehicle (DMSO 5%) followed by behavioral tests to evaluate locomotor activity, anxiolytic, antidepressant and noradrenergic system involvement. After treatment and behavioral tests, animals were euthanized and brain areas (hippocampus, striatum and prefrontal cortex) were dissected for posterior neurochemical analysis: determination of lipid peroxidation, nitrite/nitrate concentration and glutathione (GSH). According to the results, Sm shows activity in the CNS, it was possible to observe antidepressive activity similar to the antidepressant Imipramine, without alteration in locomotor activity and with the possible involvement of the noradrenergic system in this activity. Sm does not alter lipid peroxidation levels, but increases nitrite/nitrate levels at the dose of 5 mg/kg, which may explain the increase in antioxidant activity (GSH) at the same dose. Therefore, Sm presents a potential strategy for more elaborate studies and thus be used in the therapy of neurobehavioral disorders.